Kontroversen in der internationalen Waehrungspolitik. Retrospektive zu Keynes-White-Boughton und IMF - Elke Muchlinski (Intervention. Zeitschrift fuer Ökonomie / Journal of Economics, 2005)
– This paper provides textual evidence that Boughton's interpretation of Keynes's proposals for shaping the international monetary system of the post-war period misses the point. I want to investigate two points which contradict Boughton's interpretation published by the International Monetary Fund. Boughton states that White won the battle against Keynes because White was determined to create a multilateral system whereas Keynes favoured bilateral financial support to Britain by the U.S.A. I submit that Keynes's view on the function of the International Clearing Union (I.C.U.) was first of all to encourage both creditor and debtor countries to avoid trade imbalances. Second, as Keynes mentioned, the I.C.U. was not to be implemented as a "multiplicity of bilateral arrangements". Here we find the thrust of his view of the post-war period – avoiding bilateral arrangements because he believed that bilateralism could cause a new war.
Keywords: E22; E25; E12; F32; F33; 330